2015
DOI: 10.1371/journal.pone.0134054
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Dual Infected LTNP-EC Patients Developed an Unexpected Antibody Cross-Neutralizing Activity

Abstract: This study evaluated the neutralization breadth in dually infected (DI) HIV-1 long-term non-progressor elite controller patients (LTNP-EC) using a representative minipanel of 6 viruses from 5 different subtypes. Our results showed an improved neutralization breadth in DI LTNP-EC patients when compared with matched LTNP single-infected patients. The role of viral diversity in neutralization was estimated with the Shannon Entropy and the p-distance in viral quasispecies. We found a positive correlation between n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 23 publications
2
5
0
Order By: Relevance
“…The role of viral diversity driving bNAb induction has been previously described in chronically infected patients (54)(55)(56). In the present study, we have observed in patients within the first year of HIV-1 infec-…”
Section: Discussionsupporting
confidence: 68%
“…The role of viral diversity driving bNAb induction has been previously described in chronically infected patients (54)(55)(56). In the present study, we have observed in patients within the first year of HIV-1 infec-…”
Section: Discussionsupporting
confidence: 68%
“…The occurrence of SI several years after primary infection of NYU6501 may have hit an already impaired immune system, not able to further boost the antibody response. In addition to the timing of SI, viral diversity was shown to correlate with the development of a strong immune response [ 13 , 14 ]. Of interest, NYU6564 is both stimulated with a genetically more distant strain compared to NYU6501 (20% versus 17%) and also comes up with diverse env populations post-SI.…”
Section: Discussionmentioning
confidence: 99%
“…Since SI cannot be accurately timed in NYU6501, diversity data immediately post-SI remains obscure. It is possible that the short interval of ART during pregnancy lowered viral load and diversity, both known to drive a strong immune response [ 13 , 14 , 51 ]. The genetic distance analysis of NYU6501 further revealed that the new population detected after SI significantly differs in env and gag , but not in pol with a distance of only 2% compared to viruses pre-SI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations